The Relationship Between Family Support And Medication Adherence Among Type II Diabetic Patients - Sri Wahyuni Pakaya; Ansar Katili; Ita Sulistiani Basir (PT.Mantaya Idea Batara, 2024)
Diabetes Mellitus is a chronic metabolic disorder characterized by high bloodsugar levels. Consequently, this condition can cause various problems andcomplications, so patients’ medication adherence is essential to preventcomplications. Apart from that, family support is also a factor that affectsincreasing medication adherence in type 2 DM patients. This research wasclassified as quantitative research using a descriptive correlation method witha Cross-sectional design. The research population was all type 2 DM patientswith complications in the working area of Puskesmas (Public Health Center)Kabila, with as many as 516 people. In the meantime, the samples were 84people determined through Accidental Sampling. The research findingsindicated that 59 respondents (70.2%) had good family support, while 25respondents (29.8%) had poor one. Meanwhile, 48 respondents (57.1%)adhered to taking medication, whereas 36 respondents (42.9%) didnot.Additionally, the results of statistical tests using chi-square denoted a pvalue = 0.000 <?=0.05.In conclusion, there is a relationship between familysupport and medication adherence in type 2 diabetes Mellitus patients withcomplications in the working area of Puskesmas Kabila. Therefore, it isrecommended that this research be used as reference material, and futureresearchers can develop research related to factors affecting medicationadherence.